2017
DOI: 10.1002/ffj.3426
|View full text |Cite
|
Sign up to set email alerts
|

Critical comparison of selected olfactometric methods for the determination of impact odorants. Proposal of a new representation of olfactometric results

Abstract: Representation of olfactory data is a key parameter in GC‐O to simplify interpretation. Actual presentation of hybrid results, taking into account both detection frequency and odor intensity, can be improved to be more informative. We propose in this study a new way of representing olfactograms taking into account the three dimensions: detection frequency, odor intensity and odor description using bubble charts. Odor description is represented by colors that were associated to the 25 olfactory families defined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…The results were plotted in bubble charts taking into account the three dimensions: detection frequency, intensity and odour description as described in a paper elsewhere. 42,43 Detection frequency is represented on the Y axis, the bubble size is proportional to the perceived intensity, and the colour represents the olfactive family. In this study, 12 olfactive families were reported by the panellists: balsamic/vanillic, floral/white, aromatic/agrestic, aromatic/minty, sulfury, sulfury/fruity, sulfury/culinary, citrus, aldehydic, spicy, woody and green.…”
Section: Gc-omentioning
confidence: 99%
See 1 more Smart Citation
“…The results were plotted in bubble charts taking into account the three dimensions: detection frequency, intensity and odour description as described in a paper elsewhere. 42,43 Detection frequency is represented on the Y axis, the bubble size is proportional to the perceived intensity, and the colour represents the olfactive family. In this study, 12 olfactive families were reported by the panellists: balsamic/vanillic, floral/white, aromatic/agrestic, aromatic/minty, sulfury, sulfury/fruity, sulfury/culinary, citrus, aldehydic, spicy, woody and green.…”
Section: Gc-omentioning
confidence: 99%
“…We proposed recently a new way of representing the results taking into account detection frequency, intensity and olfactive description. 42,43 Thus, the aim of this work was (i) to confirm the qualitative composition of the essential oil of Timur fruits and to provide reliable quantitative data, (ii) to understand the impact of crop, supplying zone and process on the volatile analytical composition and on the aromatic profile, (iii) to identify the key olfactive constituents of the ingredients by olfactometry and (iv) to identify and accurately quantify the thiols if present. Deuterated internal standards were synthetized according to the procedure reported by Kotseridis et al 44…”
mentioning
confidence: 99%